Effect of heating rate on the pyrolysis of camel manure - Prakash Parthasarathy (10159511) (2022)
Information on the pyrolysis degradation kinetics of feedstock is critical for the design and fabrication of pyrolysis reactors. In this study, the pyrolytic behaviour of a novel biomass, camel manure, has been studied in a non-isothermal thermogravimetric analyser. The thermal analyses were performed from room temperature to 950 °C at different heating rates (10, 20, and 50°C/min) in an N2 environment (100 ml/min). The kinetic parameters of the manure components are determined using an Arrhenius model equation, and the influence of heating rate on the pyrolytic characteristics and kinetic parameters of the manure components has been examined. The results indicated that the increase in heating rates increased the starting and ending temperatures (decomposition) of manure components. The increase in heating rates shifted the ignition, peak, and burnout temperatures to higher temperatures. At the same time, the increase in heating rates improved the char yield from 22.50 to 31.51%. However, the increase in heating rates showed an insignificant effect on the kinetic parameters of the camel manure components. Other Information Published in: Biomass Conversion and Biorefinery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s13399-021-01531-9